(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
The results of studies on the biodiversity of the kurgan flora in west Pontic grass steppe of the Black Sea Lowland (the western part of Kherson region) are presented. Twenty-six of about 183 kurgans higher than 3 m, distributed over an area of approx. 3280 km2, were surveyed. The kurgan flora in the grass steppe contained more species than in the desert steppe, and was estimated at 352 species. The number of species on particular kurgans ranged from 72 to 141, 110 on average. Anthropogenic influences, such as the immediate vicinity of cultivated fields, contributed significantly to the penetration of synanthropic species, particularly therophytes, from the neighbouring habitats to the kurgans. Short-living plants: one, two or three years old were predominant (43%), phanerophytes accounted for only 5% of the kurgan flora. Halophyte species were much less numerous here than in the desert steppe. Species of alien origin, i.e. archaeophytes and kenophytes, constituted 30% of the kurgan flora. A total of 28 syntaxa of a higher rank were represented in all the kurgans studied. As in the case of the desert steppe, species belonging to classes Festuco-Brometea and Stellarietea mediae were predominant in the grass steppe, which also confirmed the semi-natural character of the kurgan flora. The species of particularly high floristic value were: Amygdalus nana, Astragalus borysthenicus, A. dasyanthus, A. pallescens, Cerastium ucrainicum, Dianthus lanceolatus, Ephedra distachya, Eremogone rigida, Galium volhynicum Hyacinthella leucophaea, Linaria biebersteinii, Phlomis hybrida Prangos odontalgica, Ranunculus scythicus, Stipa capillata, S. lessingiana, S. ucrainica and Tulipa biebersteiniana. The species encountered on the kurgans comprised 22% of the total flora of steppes in Ukraine, and about 56% of the flora of the Ascania Nova Biosphere Reserve. Kurgans are protected by law as archaeological sites. Taking all of this into account, kurgans, which constitute refugia for the steppe flora, should also be put under protection as nature monuments. Kurgans, which are uniformly distributed in the steppe zone, can play an important role in the local restoration of the plant cover that had been practically destroyed on the steppe plains (and differs from the better preserved steppe vegetation of balkas and ravines).